Therapeutic drug monitoring of gabapentin in various indications. (19th February 2019) - Larsen Burns, Margrete; Kinge, Einar; Stokke Opdal, Mimi; Johannessen, Svein I.; Johannessen Landmark, Cecilie
Abstract : Objectives: Gabapentin has been increasingly used in various indications in recent years. Despite variable pharmacokinetics, therapeutic drug monitoring (TDM) is scarcely described in other indications than epilepsy. The aim of the study was to investigate the use and pharmacokinetic variability of gabapentin in epilepsy and non‐epilepsy indications and to further evaluate the use of TDM in patients with restless legs syndrome (RLS). Materials & Methods: Population‐based data from the Norwegian Prescription Database, retrospective TDM data from the section for Clinical Pharmacology, the National Center for Epilepsy, Norway, and prospective observational data on patients with RLS were used. Results: The use of gabapentin increased by 30% from 2014 to 2017 (32 181 to 42 675 users). TDM data from 120 patients showed a 22‐fold pharmacokinetic variability in concentration/dose ratios, and this ratio was elevated in elderly patients (≥65 years). The majority of elderly used gabapentin for non‐epilepsy indications. In patients with RLS, intake in the evening/night only was common due to nocturnal symptoms, in contrast to regular dosing regimens in epilepsy. Thus, drug fasting concentrations do not reflect concentrations at the time of required therapeutic effect. TDM was still found useful in most patients to support dosage increase or evaluate adverse effects. Conclusion: Due to extensive pharmacokinetic variability, TDM can benefit patients using gabapentin. Challenges with applying TDM in new indications such as RLS include different dosage regimens and consequently different interpretation of serum concentrations. Thus, TDM should be requested on clear clinical grounds and the service tailored according to the therapeutic indication.